2012
DOI: 10.1177/1545968312445910
|View full text |Cite
|
Sign up to set email alerts
|

Resting State Changes in Functional Connectivity Correlate With Movement Recovery for BCI and Robot-Assisted Upper-Extremity Training After Stroke

Abstract: FCC may predict the steepness of individual motor gains. Future training could therefore focus on directly inducing these beneficial increases in FC. Evaluation of the treatment groups suggests that MI is a potential facilitator of such neuroplasticity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
215
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 225 publications
(235 citation statements)
references
References 46 publications
12
215
1
1
Order By: Relevance
“…One study examined the effects of upper-extremity robot-assisted rehabilitation versus an EEG-BCI approach on the relationship between functional reorganization and behavioural outcomes in patients with stroke. Restingstate fMRI analysis showed that BCI training elicited increases in functional connectivity in ipsilesional and contralesional motor cortices, the SMA, parts of the visuospatial system and the cerebellum, and that these changes were associated with motor recovery 144 . The goal of such BCI studies is to combine neurofeedback with functional stimulation to restore lost connections between the brain regions that are involved in intention, planning and movement as a behavioural treatment to aid in the transfer of the learned effect to improvements in movement outside the laboratory.…”
Section: Rehabilitation In Strokementioning
confidence: 99%
“…One study examined the effects of upper-extremity robot-assisted rehabilitation versus an EEG-BCI approach on the relationship between functional reorganization and behavioural outcomes in patients with stroke. Restingstate fMRI analysis showed that BCI training elicited increases in functional connectivity in ipsilesional and contralesional motor cortices, the SMA, parts of the visuospatial system and the cerebellum, and that these changes were associated with motor recovery 144 . The goal of such BCI studies is to combine neurofeedback with functional stimulation to restore lost connections between the brain regions that are involved in intention, planning and movement as a behavioural treatment to aid in the transfer of the learned effect to improvements in movement outside the laboratory.…”
Section: Rehabilitation In Strokementioning
confidence: 99%
“…Training‐induced changes in resting‐state networks in the healthy adult brain have also been reported following motor training (Lewis, Baldassarre, Committeri, Romani, & Corbetta, 2009; Taubert, Lohmann, Margulies, Villringer, & Ragert, 2011), cognitive training (Jolles, van Buchem, Crone, & Rombouts, 2013; Mackey, Miller Singley, & Bunge, 2013; Takeuchi et al., 2013), and physical activity in the elderly (Voss, 2010). In clinical populations, rsFC has also been used to identify changes in resting‐state networks induced by rehabilitation for multiple sclerosis (de Giglio et al., 2016) and stroke (Fan et al., 2015; Varkuti et al., 2013). …”
Section: Introductionmentioning
confidence: 99%
“…A greater reduction in intrinsic FC between ipsilesional and contralesional M1 was associated with greater gains in motor function after 12 weeks of robot-aided motor rehabilitation [126]. In relation to motor imagery, FC changes involving SMA, ipsilesional and contralesional M1, visual areas and cerebellum, predicted individual gain in motor function [127]. Following a skill acquisition program, improvement was associated with increased influence on bilateral PMC and ipsilesional M1 [108].…”
Section: Functional Connectivity Of Brain Networkmentioning
confidence: 99%
“…Intrinsic FC outcomes have been investigated in relation to a few interventions in stroke survivors: robot-aided motor rehabilitation [126]; brain-computer interface with motor imagery [127]; noradrenergic stimulation [123]; and an upper extremity accelerated skill acquisition program [108]. A greater reduction in intrinsic FC between ipsilesional and contralesional M1 was associated with greater gains in motor function after 12 weeks of robot-aided motor rehabilitation [126].…”
Section: Functional Connectivity Of Brain Networkmentioning
confidence: 99%